Virtualization as a phenomenon of educational space - Lukashchuk , Svitlana (Psychological Prospects Journal, 2021)
Purpose. To implement a theoretical analysis of virtualization as a phenomenon of educational space, to reveal the concept of virtualization in the educational environment system, to indicate the characteristic properties of virtual space; to analyze the role of the phenomenon of virtualization in learning process and comprehensive personality’s development. Methods. To achieve the goal of the study general-scientific theoretical methods of information research were used, such as: analysis, synthesis, abstraction, generalization, induction, deduction, explanation and classification. Results. An attempt is made to analyze the phenomenon as a natural component of the life-creation of subjects of the educational space, which is due to a system of technogenic, socio-cultural and economic factors. It is indicated that the visualization of the educational process makes it possible to manifest a new social environment, thus becoming a starting point for fundamental transformations of the educational process. It is determined that the virtual nature itself has a different character - virtualization,mediated by an individual or a machine. In the first case, the phenomenon arises up in the process of direct cooperation of the subjects of the educational process. The second case of increase of virtualization of the educational space supposes reduction of the interpersonal communication of participants of collective, independent mastering of educational material, the use of person’s gadgets as substitutes for subjects of the educational process. The characterological properties of the virtual space according to D.Ivanov are pointed out: The unimportance of influence (the image creates effects characteristic of reality); conditionality of qualities and features (artificial and impermanent objects); ephemerality (freedom of entry / it provides an opportunity to interrupt and restore the presence). The role of the phenomenon of virtualization in the process of learning and comprehensive personality development is analyzed, which allows not only to carry out lifelong education and self-development throughout life but also to navigate and function successfully as a professional in the modern information world. Conclusion. Conclusions are made in the system of considering the topic of virtualization as a phenomenon of educational space that informatization and computerization of education, widespread use of the global Internet will generally lead to radical changes in the education system as a whole.